Determinant of Hospital Employees Performances: A Dynamic Capability Theory Perspective with Electronic Information System Moderation - Farizal, Bembi; Adam, Mohamad; Andriana, Isni; Ichsan Hadjri, Muhammad (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to explore the effect of competence and adaptablity on hospital employee performance moderated by electronic information system. This study applied quantitative method and causally associative approach. Employees that work in Regional General Hospital (RSUD) of South Sumatera Province were being populations in this study. The study sample was 120 employees was chosen using purposive sampling. Survey methods are used in data collection, employees are given questionnaires to complete. SmartPLS is utilized for data analysis, which employs partial least squares-structural equation modeling (PLS-SEM). The results show significant effect of competence, and electronic information system on hospital employee performance. While, adaptability did not have a significant effect on hospital employee performance in South Sumatra Provincial Hospital. Electronic information system is able to strengthen moderated the effect of competence and adaptability on hospital employee performance. This study highlights the significance various aspects of competency and flexibility in handling innovation for practitioners and policymakers, as well as the effect of hospital staff. These findings can be used by managers and policy makers to improve their resources and abilities to manage innovation more effectively, which is one of the top priorities of Regional General Hospitals (RSUD) in South Sulawesi Province nationally.